Le travail social: théories, méthodologies et pratiques - Dorvil, Henri; Harper, Elizabeth; Bibliothèque numérique canadienne (Firme) (Presses de l'Université du Québec, 2013)
"Ce livre vise à introduire de nouvelles façons de concevoir, de théoriser et d'intervenir sur le social en ce xxie siècle. Il y est non seulement question des fondements du travail social, mais aussi des politiques sociales, des méthodes d'intervention et des enjeux contemporains de la profession. En revisitant d'une manière créative les postulats de base du travail social, les auteurs proposent des lectures inédites des problèmes sociaux, un regard plus nuancé sur les populations marginalisées, un renouvellement des politiques sociales comme levier de citoyenneté ainsi que des pistes d'intervention plus respectueuses des individus, des groupes, des familles et des communautés."– Site de l'éditeur.
Le texte de Vatz-Laaroussi, Michèle, 2013. « L’approche interculturelle » et Pullen-Sansfaçon, Annie, 2013. « La pratique anti-oppressive » ont été donné en lecture a cours SEX2283.
Keywords: approche interculturelle; approches et analyses; cours; discipline; histoire et politique; intersectionnalité; outils; ouvrages de références; premier cycle; sciences humaines; sciences sociales; sex2283; thématiques; travail; travail social

Gendered fields: Women, men, and ethnography - Karim, Wazir-Jahan Begum; Bell, Diane; Caplan, Pat (Routledge, 2013)
Examines and explores the progress of feminist anthropology, the gendered nature of fieldwork itself, and the articulation of gender with other aspects of the persona of the ethnographer.
Keywords: anthropologie; approches et analyses; discipline; ethnographie; genre; outils; ouvrages de références; point de vue situé; sciences humaines

Geographies of privilege - Twine, France Winddance; Gardener, Bradley (Routledge, 2013)
How are social inequalities experienced, reproduced and challenged in local, global and transnational spaces? What role does the control of space play in distribution of crucial resources and forms of capital (housing, education, pleasure, leisure, social relationships)? The case studies in Geographies of Privilege demonstrate how power operates and is activated within local, national, and global networks. Twine and Gardener have put together a collection that analyzes how the centrality of spaces (domestic, institutional, leisure, educational) are central to the production, maintenance and transformation of inequalities. The collected readings show how power–in the form of economic, social, symbolic, and cultural capital–is employed and experienced. The volume's contributors take the reader to diverse sites, including brothels, blues clubs, dance clubs, elite schools, detention centers, advocacy organizations, and public sidewalks in Canada, Italy, Spain, United Arab Emirates, Mozambique, South Africa, and the United States. Geographies of Privilege is the perfect teaching tool for courses on social problems, race, class and gender in Geography, Sociology and Anthropology.
Keywords: afrique; afrique du sud; amériques; anthropologie; approches et analyses; canada; classe sociale; discipline; environnement; espagne; europe; géographie; italie; mozambique; outils; ouvrages de références; privilèges; racisme; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; émirats arabes unis; états-unis